Fiqh Study on Muslim/Muslim Women's Clothing and Its Relation to the Problem of Aurat (Pornography and Pornoaction) - Mukhlis Akbar Ramadhani; Dinda; Mirale Harahap (Jurnal Cendikia ISNU SU, 2025)
Muslim and Muslim women's clothing from the perspective of Islamic fiqh has an important role in maintaining self-honor and enforcing the obligation to cover the awrah in the midst of the development of modern society which is colored by the rampant phenomenon of pornography and pornography. In Islam, clothing not only serves as a body covering, but also as a manifestation of obedience, Islamic identity, and an instrument of moral and social protection. The difference in the limits of aurat between men and women as well as the criteria for dressing in accordance with sharia are the normative basis in regulating the dress etiquette of Muslims. This research aims to examine the concept of Muslim and Muslim women's clothing from the perspective of Islamic fiqh and analyze its relationship with the issues of aurat, pornography, and pornography in the context of modern life. The research method used is normative qualitative research with a literature study approach, through analysis of Islamic legal sources in the form of the Qur'an, hadith, and the views of classical and contemporary scholars. The results of the study show that clothing provisions that are in accordance with sharia, such as covering the aurat, not being strict, not transparent, and not resembling clothes of the opposite sex, have a significant role in preventing social slander and minimizing the potential for pornography and pornography. From the perspective of fiqh, violations of dress ethics are not only seen as a moral issue, but also as a violation of the law that has an impact on the social and spiritual order of Muslims. In conclusion, Muslim and Muslim women's clothing in accordance with the provisions of sharia is an important instrument in maintaining the purity of the awrah and social order. Therefore, continuous education and socialization efforts are needed regarding the concept of aurat and the ethics of dressing in Islam through educational institutions, media, and public policy to strengthen the awareness and compliance of the ummah with Islamic sharia values.